FROM DAMSELS IN DISTRESS TO AGENTS OF CHANGE: THE EVOLUTION OF FEMALE PORTRAYAL IN BOLLYWOOD - Dr. Abha Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The portrayal of women in Bollywood cinema has undergone a significant transformation over the decades, reflecting broader societal changes and evolving gender norms. From the early days of Indian cinema, where women were often depicted as damsels in distress—passive, submissive, and reliant on male saviors—to the contemporary era where female characters are increasingly portrayed as strong, independent, and agents of change, Bollywood has mirrored and sometimes challenged the prevailing attitudes towards women in Indian society. This paper explores the evolution of female representation in Bollywood, tracing the journey from stereotypical roles to more nuanced and empowering characters. It examines key films and characters that have marked pivotal shifts in this evolution, analyzing how these portrayals have influenced and been influenced by the changing roles of women in Indian society. The study also considers the impact of feminist movements, globalization, and the rise of female filmmakers in shaping a new narrative for women in Bollywood. Ultimately, this paper argues that while significant progress has been made, the journey towards fully realized and diverse female characters in Bollywood is ongoing, with the industry continuing to grapple with issues of representation, stereotyping, and gender equality.